Avaliação e estimativas de polinização cruzada, heterozigosidade e heterose em variedades sintéticas de cebola (allium cepa l.) - Alves, Ítala Layanne de Souza (2019)
The present study aimed to the develop and evaluate of Synthetic Varieties (VS) Syn 0 of onion, as an alternative to the development of hybrids for Brazilian northeast, as well to estimate of cross pollination and heterozygosity rates in onion populations. Eight Open Pollinated (OP) populations were used to obtain six VS. Populations of yellow bulb were planted in alternating rows with populations of red colour bulb, dominant trait. Four microsatellite loci, AMS 03, ACM 004, ACM091 and ACM124, were additionally used in the cross-pollination rate estimates for four crosses. Heterozygosity was estimated with PowerMarker V3.25 software support. Cycle were evaluated the total (PTB) and commercial bulb yields (PBC) and the maturation cycle. Mean heterosis, heterobeltiosis and standard heterosis were estimated for the yield of bulbs. Six VS, eight open pollinated populations and one commercial hybrid were evaluated in a randomized complete block design with three replicates in two different times. Crossing rates estimated with morphological marker ranged from 15% to 39%, with a mean of 28.2%, and with microsatellite loci ranged from 33% to 71%, with an average of 42.7%. The mean values of heterozygosity in eight populations ranged from 0.82 to 1.0. The mean heterosis for VS commercial bulb yield was negative in the first semester and positive in four VS in the second semester. The value of heterobeltiosis for PBC was negative in the first semester and positive in three VS in the second semester. The VS did not present superior heterosis in relation to the standard commercial cultivar, BRS Alfa São Francisco, except to VS Alfa RT x BRS Alfa São Francisco in the first semester. Significant effects were observed for cultivars and cultivars*semester interaction for the three variables. The commercial hybrid and Alfa RT presented the highest pooled averages for PTB, 72.8 and 73.9 t / ha-1, respectively, while VS Cascuda T6 x Botucatu and Cascuda T6 showed the lowest yields. For maturation, the highest precocity cultivars were Alfa RT, in the first semester and Vale Ouro IPA11 in the second semester. The synthetic varieties Syn-0 BRS Alfa SF x Valley Ouro IPA11, Alfa RT x BRS Alfa SF, BRS Rio Vale x BRS Carrancas and Botucatu x BRS Carrancas presented a statistically similar PBC average to four cultivars. In general, VS presented low values of heterosis and low yield potential to replace commercial OP and hybrid populations.